Trastorno de la expresión escrita en el proceso de enseñanza aprendizaje de educación básica media - Chicaiza Lovato, Juan Daniel (2017)
The present researching determined that the disorder of written expression affects learning students', for this reason the following objective was proposed: To diagnose the level of disorder incidence on teaching-learning process of the Basic Education students of the Educational Unit "Pelileo".The causes of this influence one the limited or not use of techniques and active methodologies by the teachers in the teaching-learning process considering that each child is a different world, this also transcends in the performance in other areas of study. For this reason Basic General Education is responsible for developing skills, abilities, skills and study strategies to achieve the students' logical thinking and thus minimize the impact of such influence. For this project, two research modalities were executed: the first was quantitative, where statistical data were collected from the surveys applied to students and teachers; the second modality was the descriptive investigation where important characteristics of the mentioned disorder were determined. The second modality was the descriptive investigation where important characteristics of the mentioned disorder were determined. The survey technique was carried out with its respective data collection instruments: it was executed with a population made up of 33 students and 8 teachers from the mentioned campus.